Management in cases of instruments fractured in the root canal system - Olczak, Katarzyna; Pawlicka, Halina (Journal of Stomatology, 2016)
Introduction. Fracture of instruments in the lumen of the root canal is a frequent complication during endodontic treatment. If possible, we should remove the separated fragment using an array of available methods. If the removal is associated with too much risk, other procedures should be implemented. Aim of the study. To present various protocols in cases of instrument separation in the root canal based on the description of case studies. Material and methods. The study presents the removal of broken canal instruments using ultrasounds as well as a case of preparation and obturation of a canal with an instrument broken at the tip of the root. The authors have also reviewed the literature regarding different methods of the removal and handling of broken canal instruments. Results and conclusion. In each case, potential benefits and complications associated with leaving or removing a broken instrument should be considered. In many cases, ultrasonics technique is very useful in removingseparated fragments.